Disease Burden of Patients with Asthma/COPD Overlap in a US Claims Database: Impact of ICD-9 Coding-based Definitions. (30th March 2017) - Wurst, Keele E.; St. Laurent, Samantha; Hinds, David; Davis, Kourtney J.
ABSTRACT: The inclusion of an asthma/chronic obstructive pulmonary disease (COPD) overlap syndrome (ACOS) population in the 2015 Global Initiative for Chronic Obstructive Lung Disease strategic documents has raised questions about the profile of these patients in clinical practice, as they are mostly excluded from asthma and COPD clinical trials. We estimated the disease burden, co-morbidities, and respiratory treatments of patients with asthma/COPD overlap, utilizing the Truven MarketScan commercial and Medicare databases. Patients with ≥1 COPD or chronic obstructive asthma diagnostic code were identified between January 1, 2008, and December 31, 2011. The asthma/COPD overlap group was defined and stratified based upon type and frequency of asthma diagnostic code (chronic obstructive asthma only, COPD and chronic obstructive asthma, and COPD and ≥1 asthma code). 1, 488, 613 patients were identified; of these, 1, 171, 626 were diagnosed with COPD alone and 316, 987 with asthma/COPD overlap. Patients with asthma and COPD had higher disease burden indicators and inhaled corticosteroid/long-acting beta-agonist use compared with COPD alone. This trend was consistent for all definitions of asthma/COPD overlap. Patients with obstructive asthma and COPD tended to be older, with greater disease burden compared with other definitions; this population may represent a more severe form of asthma/COPD overlap. Disease burden and treatment also varied based on the codes defining asthma/COPD overlap, indicating possible phenotypic differences. More clinical insight and detailed phenotyping is needed to determine the reasons for coding variation in asthma/COPD overlap, with implications for further research to address unmet needs.